Heartstopper. Volume 5 - Oseman, Alice; Graphix (Firm); Scholastic Inc. (2023)
Nick and Charlie are in love. But what happens next?
Boy meets boy. Boys become friends. Boys fall in love. Shy and softhearted Charlie Spring sits next to rugby player Nick Nelson in class one morning. A warm and intimate friendship soon follows, and that soon develops int something more for Charlie, who doesn't think he has a chance. But Nick is struggling with feelings of his own, and as the two grow closer and take on the ups and downs of high school, they come to understand the surprising and delightful ways in which love works.
11-13 years old.
Keywords: Gay high school students -- Comic books, strips, etc; Bisexual high school students -- Comic books, strips, etc; Lesbian high school students -- Comic books, strips, etc; High schools -- Comic books, strips, etc; High school students -- Comic books, strips, etc; Male friendship -- Comic books, strips, etc; Interpersonal relations -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Gay teenagers -- Comic books, strips, etc; Rugby football players -- Comic books, strips, etc; Gay comics; Queer comics; School comics; Romance comics; Comics (Graphic works); Graphic novels